When Shikamoo Mama/Baba replaces Tukuwoni Mawu/Dadi: An account of shifting access rituals among the Ngoni of Tanzania - Mapunda, Gastor; Sommer, Gabriele (Linguistik Online, 2017)
The current paper is an attempt at providing an ethnographic description of Tanzanian Ngoni access rituals (greetings) considering verbal and visual aspects of these communicative rou-tines. Three methods of data collection were used, namely: role-play, semi-structured inter-view, and observation. The role-plays were used in order to see how the Ngoni apply their knowledge of this kind of access ritual still acquired in the course of growing up in their communities. Role-plays were recorded with a digital camcorder after the interviews had tak-en place. Semi-structured interviews were meant to provide insights into diachronic develop-ments such as how the expression of politeness through greetings may have changed. Obser-vation method was meant to capture behavioural patterns shown during greeting exchanges and notes were taken immediately thereafter. The main findings are that due to pervasive con-tact between Ngoni and Swahili, greetings tend to be brief today and there is a widespread use of code-switching by all age groups. The tendency to prefer Swahili is viewed by older mem-bers of the community as lack of respect whereas the younger generations regard the use of Swahili as more appropriate and as a reflection of social changes that have been taking place in the community.